Preclinical characterization of the Omicron XBB.1.5-adapted BNT162b2 COVID-19 vaccine - Kayvon Modjarrad; Ye Che; Wei Chen; Huixian Wu; Carla I. Cadima; Alexander Muik; Mohan S. Maddur; Kristin R. Tompkins; Lyndsey T. Martinez; Hui Cai; Minah Ramos; Sonia Mensah; et al. (npj Vaccines)
Abstract As SARS-CoV-2 evolves, increasing in potential for greater transmissibility and immune escape, updated vaccines are needed to boost adaptive immunity to protect against COVID-19 caused by circulating strains. Here, we report features of the monovalent Omicron XBB.1.5-adapted BNT162b2 vaccine, which contains XBB.1.5-specific sequence changes, relative to the original BNT162b2 backbone, in the encoded prefusion-stabilized SARS-CoV-2 spike protein (S(P2)). Biophysical characterization of Omicron XBB.1.5 S(P2) demonstrated that it maintains a prefusion conformation and adopts a flexible, predominantly open, state, with high affinity for the human ACE-2 receptor. When administered as a 4th dose in BNT162b2-experienced mice, the monovalent Omicron XBB.1.5 vaccine elicited substantially higher serum neutralizing titers against pseudotyped viruses of Omicron XBB.1.5, XBB.1.16, XBB.1.16.1, XBB.2.3, EG.5.1 and HV.1 sublineages and phylogenetically distant BA.2.86 lineage than the bivalent Wild Type + Omicron BA.4/5 vaccine. Similar trends were observed against Omicron XBB sublineage pseudoviruses when the vaccine was administered as a 2-dose series in naive mice. Strong S-specific Th1 CD4+ and IFNγ+ CD8+ T cell responses were also observed. These findings, together with real world performance of the XBB.1.5-adapted vaccine, suggest that preclinical data for the monovalent Omicron XBB.1.5-adapted BNT162b2 was predictive of protective immunity against dominant SARS-CoV-2 strains.